Quality of sleep among caregivers of Alzheimer disease patients: cross-sectional study from Saudi Arabia - Alhazzani, Adel Ali; Alqahtani, Mohammed Saeed (International Journal Of Community Medicine And Public Health, 2021)
Background: Alzheimer’s disease (AD) is the most common cause of dementia and represents a major health burden. Characterized by gradual decline in cognitive function, leading to dependency and changes in behavior and personality. Patients with AD need continuous care, which may affect the caregiver’s quality of life, including sleep quality. The aim of this study was to assess sleep quality among AD patients’ caregivers and its determinants in Aseer region, Saudi Arabia. Methods: A descriptive cross-sectional study was conducted among 110 caregivers of AD patients at Abha Mental Health Hospital. The caregivers’ sleep quality was assessed using the Pittsburgh Sleep Quality Index (PSQI). A global PSQI cutoff value of 5 or higher was considered as indicative of poor sleep quality. Results: Female caregivers’ constituted 53.6% of the sample, and 50% were below the age of 40 years. The majority of the caregivers (64.5%) reported that they had experienced sleep disturbances during past month and 10% needed medication approximately three or more times a week to help them sleep. Almost two-thirds of the caregivers (60%) spent more than 10 hours daily with their patients. Regarding sleep hygiene, 40.9% of the caregivers rated their sleep quality as poor and only 10.9% had good sleep quality. Conclusions: The burden on caregivers of AD patients is considerable and often under-recognized; in particular; most caregivers in the Saudi population were young and of working age. Poor sleep quality affected the caregivers’ day life activities but typically remained undertreated.